Office cervicoscopy versus stationary colposcopy in suspicious cervix: A randomized controlled trial - Atef Mohammad Darwish; Momen Ahmad Kamel; Kamal Zahran; Mostafa Aboulela (Journal of Mid-Life Health, 2019)
Study Objective: The objective of the study was to estimate the diagnostic accuracy and doctor satisfaction of small caliber office cervicoscopy versus stationary colposcopy in diagnosis of ectocervical as well as endocervical lesions in women clinically presented with suspicious cervix. Patients and Methods: Eligible 112 cases with clinically suspicious cervix were randomized into Group A (56 cases) and Group B (56 cases) who were subjected to small caliber office cervicoscopy and stationary colposcopy, respectively. The outcome was the diagnostic accuracy and safety of both tools for detection of ectocervical and endocervical cervical lesions. Results: There was no statistically significant difference between both groups regarding parity, previous abortion, age at marriage, duration of marriage, and age at menarche and menopause. On unaided naked eye examination of the cervix (UNEE), there were no statistically significant differences between both groups. Diagnostic indices were similar in both groups apart from the finding that office cervicoscopy was more sensitive for detection of endocervical abnormalities. Doctors were significantly more satisfied with stationary colposcopy than office cervicoscopy. Conclusions: Office cervicoscopy is a good complementary tool added to stationary colposcopy for detection of cervical lesions in cases with suspicious cervix as an example of high-risk group for cervical cancer. Due to its small caliber, cervicoscopy offers a better evaluation of the endocervical canal, especially in cases of Type 2 and 3 transformation zone with a possibility of examination of the endometrial cavity.